Eastern Europe in the middle ages (500-1300) - Curta, Florin (Leiden, Boston : Brill, 2019)
"This book provides a comprehensive synthesis of scholarship on Eastern Europe in the Middle Ages. The goal is to offer an overview of the current state of research and a basic route map for navigating an abundant historiography available in more than 10 different languages. The literature published in English on the medieval history of Eastern Europe--books, chapters, and articles--represents a little more than 11 percent of the historiography. The companion is therefore meant to provide an orientation into the existing literature that may not be available because of linguistic barriers and, in addition, an introductory bibliography in English"-- |c Provided by publisher.
Concepts and problems -- Written and archaeological sources -- The last century of Roman power (ca. 500 to ca. 620) -- East European dark ages : Slavs and Avars (500-800) -- Migrations-real and imagined : Croats, Serbs, and Bulgars (600-800) -- Early medieval Bulgaria (680-850) -- The West in the East (800-900) -- Great Moravia -- Steppe empires? The Khazars and the Volga Bulgars -- Oghuz, Pechenegs, and Cumans : nomads of medieval Eastern Europe? -- Conversion to Christianity : Moravia and Bulgaria -- The long 10th century of Bulgaria -- New migrations : Magyars and Vikings -- The rise of Rus' -- Byzantium in the Balkans (800-1100) -- The western Balkans in the high Middle Ages (900-1200) -- New powers (I): Piast Poland -- New powers (II): Arpadian Hungary -- New powers (III): Premyslid Bohemia -- Population : size, health, migration -- Rural and urban economy -- Social organization -- The construct of a tyrant : feudalism in Eastern Europe -- The Church : ecclesiastical organization and monasticism -- The faith : religious practices, popular religion, and heresy -- The first five Crusades and Eastern Europe -- Crusades in Eastern Europe -- Literacy and literature -- Monumental art -- The rise of Serbia -- The second Bulgarian Empire -- Catastrophe, Pax Mongolica, and globalization.
Includes bibliographical references and index/Rujukan : mukasurat
Keywords: Middle Ages -- Historiography; Europe, Eastern -- History; Europe, Eastern -- Historiography